Village Government Corruption in Decentralized Indonesia: Democracy, Ethnic Diversity, and Budget Authority - batubara, rumayya (Universitas Airlangga, 2016)
The village (desa) is the lowest level of government administration in Indonesia. In the pre-decentralization, although by law a village should held a regular election to select their leader, in practice the election is highly influenced and intervened by higher level of government. The new decentralization law has provided rural village governance with free election of village head and autonomy to design and decide budget and regulation without approval from the district government. The main purpose of this paper is to investigate the determinants of corruption in village government of Indonesia in the more decentralized system of government introduced in 2001, focusing on the interrelationship between democracy and ethnic fractionalization at village level. Applying a Probit model to the IFLS (Indonesian Family Life Survey) data set on the perception of corruption incidence and the changes in governance at village government in 256 communities, this paper finds that an ethnic diversity at village level is positively associated with corruption if democracy is practiced before the decentralization, and, in contrast, is negatively associated with corruption if the democracy is newly adopted following the decentralization reform. These results are robust, with and without inclusion of budget autonomy, which found to have positive association with corruption. Keywords: Corruption, Decentralization, Democracy, Ethnic Diversity, Budget AuthorityJEL : D73, H11, Z10